PARTISIPASI MASYARAKAT DALAM REVITALISASI PASAR TRADISIONAL STUDI KASUS : PASAR SAMPANGAN KOTA SEMARANG - Rahma Anggraeni; Teguh Yuwono; Priyatno Harsasto (Journal of Politic and Government Studies, 2016)
ABSTRACTThis research aims to identify public participation in the revitalization oftraditional markets. Traditional market revitalization in Semarang City is done tomantain traditional market. This research analyzes the interaction the actor whogets involved in implementing revitalization, knowing traders involvement andsociety around this location which become attention in this research. Theresearcher chooses Sampangan Market in Semarang City as research case study.Where it will be measured how far traders and society participation they havebeen given and knowing participation proccess in implementing marketSampangan revitalization.Methods which are used in this research are combination method byqualitative and quantitative approaches and descriptive method. In data collection,researcher used interview as a research tool and the research informant wasDepartment of Market and Market Management Sampangan and then distributedquestionnaire to society and traders then it was analyzed by using likert scale.Researcher also used secondary data came from documentation data which wasprovided in Department of Market and mass media and also other literaturesources such as books and journals.Results of this research showed that revitalization had been implementedwell by government which was supported by public participation and tradersparticipation. Society and traders supported revitalization program from planningprogram until monitoring program. Based on this research results could beconcluded that public and traders participation was an important thing inimplementing each traditional market revitalization program in order to marketrevitalization program run appropriate with the goal. Every participation proccesswhich was given by society and traders impacted towards traditional marketprogram’s success. Therefore, government should always involve public andtraders participation, not only in implementing phase but hopefully untilmaintaining and monitoring phase to maintain tha market which had beenrevitalized.Keywords : Revitalization of Traditional Markets, Public Participation,Participation of Traders